The Effect of Debt to Equity Ratio (DER) on Return on Equity at PT Astra Agro Lestari Tbk - Saradillah, Linda; Alwi, Alwi; Huda, Nurul (Devitara Innovations, 2025)
This study investigates the effect of the Debt to Equity Ratio (DER) on Return on Equity (ROE) at PT Astra Agro Lestari Tbk. DER represents the proportion of debt to equity in a company's capital structure, whereas ROE reflects the company’s ability to generate profits from its shareholders’ equity. The research employs a quantitative approach using secondary data derived from the company’s annual financial statements for the period 2012–2023. A simple linear regression analysis is conducted to assess the relationship between the variables. The findings reveal that DER does not have a statistically significant effect on ROE. This indicates that changes in the company’s capital structure, particularly in terms of debt utilization, do not substantially impact the returns earned by shareholders. The study suggests that other factors—such as operational efficiency, asset utilization, and strategic financial management—may play a more prominent role in influencing ROE. These results provide valuable insights for investors and corporate decision-makers regarding the relative importance of capital structure in shaping financial performance.